Mathematical Model of Flow in a Tube with an Overlapping Constriction and Permeability. (2015) - Muthu, P.; Varunkumar, M.
Abstract: Perturbation solution is given for the laminar flow of viscous incompressible fluid through a non-uniform tube with an overlapping constriction and permeable wall. The effect of fluid reabsorption through permeable wall is considered by taking flux as a function of axial distance. The effects of various parameters on the velocity profiles at different cross sections of the tube, the axial distribution of wall shear stress, mean pressure drop and streamlines are discussed and presented graphically.